2001
DOI: 10.1103/physrevd.65.024003
|View full text |Cite
|
Sign up to set email alerts
|

Instability of extremal relativistic charged spheres

Abstract: With the question, "Can relativistic charged spheres form extremal black holes?" in mind, we investigate the properties of such spheres from a classical point of view. The investigation is carried out numerically by integrating the Oppenheimer-Volkov equation for relativistic charged fluid spheres and finding interior Reissner-Nordström solutions for these objects. We consider both constant density and adiabatic equations of state, as well as several possible charge distributions, and examine stability by both… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
90
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 19 publications
2
90
1
Order By: Relevance
“…One possibility to obtain an extremal black hole is to produce one from the collapse of an already extremal object. Previous mainly numerical studies ( [12], [7]) have concluded that when Q < M collapse always takes place at a critical radius R c outside the outer horizon, and as Q approaches M, this value approaches the horizon. This is similar to the non-charged case where the Buchdahl inequality implies that collapse will take place when R < 9M/4, i.e., R c = 9M/4, cf.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility to obtain an extremal black hole is to produce one from the collapse of an already extremal object. Previous mainly numerical studies ( [12], [7]) have concluded that when Q < M collapse always takes place at a critical radius R c outside the outer horizon, and as Q approaches M, this value approaches the horizon. This is similar to the non-charged case where the Buchdahl inequality implies that collapse will take place when R < 9M/4, i.e., R c = 9M/4, cf.…”
Section: Introductionmentioning
confidence: 99%
“…In the charged case the critical value is expected to be smaller due to the Coulomb repulsion, and this is also shown to be the case below and in particular as Q → M the stability radius does approach the outer horizon. For more information on the relation of this topic to extremal black holes and black hole thermodynamics we refer to [7], [16], [13] and [11] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the formation of Reissner-Nordström (RN) black holes, is in connection with the third law of black hole thermodynamics [2], [17], [14], because an extreme RN black hole has zero temperature. So, there is an interest on the formation of charged black holes from a pure theoretical point of view [49].…”
Section: Introductionmentioning
confidence: 99%
“…Although some of these works refer to static situations ( [3]- [5], [9,19,23,24,29,30], [32]- [34], [36,37,39,41]) there have been important efforts in describing dynamical situations too ( [6]- [8], [10]- [14], [16,17,21,22,26,40,42]). Particularly relevant for the present paper are references [14,22] and [40].…”
Section: Introductionmentioning
confidence: 99%